Detecção e caracterização do rotavírus em Aracaju/Sergipe, Brasil, 2010 a 2012 - Rodrigues, Alda (2014)
Rotavirus diarrhea is still an important cause of mortality in children worldwide, responsible each year for about 500,000 deaths. The introduction of the vaccine against the virus could lead to a reduction in morbidity and mortality associated with rotavirus. In Brazil, the Rotarix ® rotavirus vaccine, which contains the genotype G1P [8], was included in the national programme of immunization since March 2006. This project aims to evaluate clinical and epidemiological data related to infection by RVA, rotavirus genotypes prevalent. The research project is a cross-sectional study in which children with acute diarrhoea were recorded prospectively from 2010 to 2012. The location of collection of fecal samples was the Hospital of urgency of Sergipe in Pediatric Emergency sector, in Aracaju/SE. The clinical and epidemiological information was obtained through a questionnaire. The clinical severity was determined by a scoring system 20, calculated from the survey point. It was verified the episodes of acute diarrhea and stool samples collected for research and genotyping of rotavirus by ELISA and RT-PCR method.Descriptive statistical calculations were carried out to define the epidemiology of rotavirus. EIA positive results were found in 78 of the 790 samples. The most frequent genotype was G2 P [4], followed by the G8 genotype P [4], P [8] G1, G3 P [8], G1 P [6]. Mixed infections were detected G2 P [4] P [8], P [4] and G1G2 G2G8 P [4] and in general there was a cocirculação of different genotypes in the years studied, moreover, shows an alternation between the genotypes every year. The results obtained in this study observed a variability of positive cases distributed, confirming that the seasonality in the region is not remarkable. Therefore, new strains of rotavirus are emerging and associated with severe diarrhea. For this reason, monitoring is required to follow changes in the epidemiology of rotavirus.